Reality Counseling with the WDEP (Wants, Doing, Evaluation, Planning) Technique to Increase Students' Interest in Learning - Sinta Wahyu Safitri; Ni Ketut Suarni; Kade Sathya Gita Rismawan (Universitas Pendidikan Ganesha, 2026)
This research is motivated by the low interest in learning of students as indicated by the lack of active participation in learning, low motivation to complete assignments, and passive attitudes during the learning process. This condition indicates the need for guidance and counseling interventions that can foster awareness, responsibility, and intrinsic motivation of students. This study aims to describe the effectiveness of reality counseling with the WDEP (Wants, Doing, Evaluation, Planning) technique in increasing students' interest in learning. The population in this study consisted of all 26 students. The researcher applied the Purposive sampling technique in determining the research subjects. Purposive sampling is a method of selecting samples based on certain considerations or criteria. The sample used by the researcher was a class X with 6 students and a class XI with 11 students. The data collection method and instrument used in this study was a questionnaire. The data analysis technique used in this study was data analysis with a t-test. The results of the study showed an increase in students' interest in learning after being given reality counseling with the WDEP technique. The implications of this study indicate that reality counseling with the WDEP technique can be used effectively as an alternative guidance and counseling service to increase students' interest in learning.